The Effect Of Leadership Style, Motivation And Training On The Performance Of Asn Teachers In All State Vocational Schools In Situbondo Regency With Satisfaction Work As An Intervining Variable - Susiana, Susiana; Ariyantiningsih, Febri; Iqbal Anshory, Muhammad (Cita konsultindo, 2025)
The purpose of this study is to analyze the influence of variablesLeadership Style, Motivation and Training on the Performance of ASN Teachers in All State Vocational Schools in Situbondo Regency with Job Satisfaction as an Intervening Variable. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application Leadership style has a positive but insignificant effect on Job Satisfaction. Motivation has a significant positive effect on Job Satisfaction. Training has a significant positive effect on Job Satisfaction. Leadership style has a significant positive effect on Performance. Motivation has a positive but insignificant effect on Performance. Training has a positive but insignificant effect on Performance. Job satisfaction has a significant positive effect on Performance. Leadership style has a positive but insignificant effect on Performance through Job Satisfaction. Motivation has a significant positive effect on Performance through Job Satisfaction. Training has a significant positive effect on Performance through Job Satisfaction